Utilizing Wild Species for Peanut Improvement. Issue 3 (16th June 2017) - Stalker, H. Thomas
Abstract : The cultivated peanut ( Arachis hypogaea L.) is an allotetraploid species with a very large and complex genome. This species is susceptible to numerous foliar and soil‐borne diseases for which only moderate levels of resistance have been identified in the germplasm collection, but several of the 81 wild species are extremely resistant to many destructive peanut diseases. Peanut species were grouped into nine sections, but only taxa in section Arachis will hybridize with A. hypogaea . Most of these species are diploid, but two aneuploids and two tetraploids also exist in the section. The first peanut cultivars released after interspecific hybridization were 'Spancross' and 'Tamnut 74' during the 1970s from a cross between A. hypogaea and its tetraploid progenitor. However, introgression of useful genes from diploids has been difficult due to sterility barriers resulting from genomic and ploidy differences. To utilize diploids in section Arachis, direct hybrids have been made between A. hypogaea and diploid species, the chromosome number doubled to the hexaploid level, and then tetraploids recovered with resistances to nematodes, leaf spots, rust, and numerous insect pests. 'Bailey', a widely grown Virginia‐type peanut, was released from these materials, and other cultivars are gown in Asia and South America. Alternatively, hybrids between diploid A and B genome species have been made, the chromosome number doubled, and cultivars released with nematode resistance derived from Arachis species. Introgression from Arachis species to A. hypogaea appears to be in large blocks rather than as single genes, and new genotyping strategies should enhance utilization of wild peanut genetic resources.